2021
DOI: 10.31235/osf.io/fjqhs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Privacy Research: Literature Review, Framework, and Research Agenda

Abstract: The ways in which privacy is defined, perceived, and enacted are contingent on cultural, social, political, economic, and technological structures. Privacy research, however, is often conducted in settings that do not account for variations in how privacy is perceived and enacted. A comparative perspective explicitly addresses this shortcoming by requiring the contextualization of privacy through investigating structural similarities and differences. This paper outlines a comparative privacy research framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This study has revealed that natural language is promising to operationalize intercultural privacy research and comparative privacy research (Masur et al, 2021). This study connects questions from intercultural information ethical discussions (e.g., Ess, 2005; 2019; Hongladarom, 2016) with the computational textual methods, and provides a multilevel description of how privacy as an abstract concept exists in the two languages.…”
Section: Discussionmentioning
confidence: 99%
“…This study has revealed that natural language is promising to operationalize intercultural privacy research and comparative privacy research (Masur et al, 2021). This study connects questions from intercultural information ethical discussions (e.g., Ess, 2005; 2019; Hongladarom, 2016) with the computational textual methods, and provides a multilevel description of how privacy as an abstract concept exists in the two languages.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has examined antecedents of PPBs, it has rarely made clear distinctions and comparisons between the contexts in which different privacy threats arise in (Ortloff et al, 2021;Epstein & Quinn, 2020;Masur et al, 2021;Yun et al, 2019). This is a somewhat surprising omission, as context plays a major role in individuals' privacy perceptions and behaviors (Nissenbaum, 2010).…”
Section: Introductionmentioning
confidence: 99%